Negative electrode, battery and electrical equipment

By adding a porous non-carbon liquid retention agent to the negative electrode active layer of the lithium-ion battery, the problem of decreasing wetting ability of the battery electrode sheet to the electrolyte in a low-temperature environment is solved, and the low-temperature performance and cycle life of the battery are significantly improved.

CN119764336APending Publication Date: 2025-04-04CHONGQING FUDI BATTERY RES INST CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410455132.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-04-16
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

In a low-temperature environment, the electrolyte fluidity of the lithium-ion battery decreases, resulting in a decrease in the wettability of the battery pole sheet on the electrolyte, an increase in the diffusion impedance of the lithium-ion, and a significant reduction in the low-temperature performance and cycling efficiency of the battery.

Method used

Add a non-carbon liquid retention agent with a porous structure to the negative electrode active layer to replace some or all of the carbon material conductive agents, improve the porosity of the negative electrode, enhance the wettability and liquid retention ability of the electrolyte, and reduce the diffusion impedance of the electrolyte.

Benefits of technology

It improves the low-temperature performance of the battery, improves the rate performance and cycle life of the battery, avoids electrochemical side reactions, and improves the safety performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119764336A_ABST
    Figure CN119764336A_ABST
Patent Text Reader

Abstract

The present application provides a negative electrode, a battery and an electrical device, wherein the negative electrode includes a current collector and a negative electrode active layer disposed on at least one side of the current collector, the negative electrode active layer includes a non-carbon liquid retaining agent and a conductive agent, the mass ratio of the conductive agent to the mass of the non-carbon liquid retaining agent is less than or equal to 50%; or, the negative electrode active layer includes a non-carbon liquid retaining agent and does not include a conductive agent; the non-carbon liquid retaining agent has a porous structure. The non-carbon liquid retaining agent has good stability and is not prone to side reactions with the electrolyte. The present application enhances the wettability of the electrolyte in the battery pole piece by adding a non-carbon liquid retaining agent with a porous structure to the negative electrode active layer, thereby enhancing the liquid retaining capacity of the battery pole piece, reducing the diffusion impedance of the electrolyte, alleviating the polarization problem of the battery, improving the low temperature performance of the battery, and increasing the rate performance and cycle life of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The embodiments of the present application relate to the field of battery technology, and in particular to a negative electrode, a battery, and an electrical device. Background Art

[0002] Lithium-ion batteries are widely used in mobile devices such as mobile phones and laptops, as well as passenger car batteries and large energy storage equipment due to their high energy density and excellent cycle performance. During the charge and discharge process of the battery, the rapid transmission and diffusion of lithium ions are crucial to the power performance of the battery. Especially in low temperature environments, the fluidity of the electrolyte decreases, the wettability of the electrolyte to the battery pole piece decreases, the lithium ion diffusion impedance increases, and the low temperature performance of the battery decays significantly. In order to improve the wettability of the electrolyte to the battery pole piece, some methods are to add a carbon material conductive agent with a porous structure. The porous structure of the conductive agent can effectively improve the problem of slow electrolyte conduction inside the battery pole piece, but the carbon material itself is prone to electrochemical side reactions with the electrolyte, resulting in a decrease in the battery's cycle efficiency. The richer the porous structure of the carbon material conductive agent, the more side reactions it has, and the worse the battery's cycle efficiency. Summary of the invention

[0003] In view of this, the present application provides a negative electrode, a battery and an electrical device. The negative electrode selects a suitable non-carbon liquid retaining agent, which has good stability and is not easy to have side reactions with the electrolyte. The present application enhances the wettability of the electrolyte in the battery pole piece by adding a non-carbon liquid retaining agent with a porous structure in the negative electrode active layer, thereby enhancing the liquid retention capacity of the battery pole piece, reducing the diffusion impedance of the electrolyte, alleviating the polarization problem of the battery, improving the low temperature performance of the battery, and increasing the rate performance and cycle life of the battery.

[0004] In a first aspect, the present application provides a negative electrode, which includes a current collector and a negative electrode active layer arranged on at least one side surface of the current collector, the negative electrode active layer includes a non-carbon liquid retaining agent and a conductive agent, and the mass ratio of the conductive agent to the non-carbon liquid retaining agent is less than or equal to 50%; or, the negative electrode active layer also includes a non-carbon liquid retaining agent and does not include a conductive agent; the non-carbon liquid retaining agent has a pore structure.

[0005] In the embodiment of the present application, the negative electrode active layer further includes a negative electrode active material, the mass percentage of the non-carbon liquid retaining agent in the negative electrode active layer is 0.5%-5%; the mass percentage of the negative electrode active material in the negative electrode active layer is 95%-99.5%.

[0006] In the embodiment of the present application, the pore volume of the non-carbon liquid retaining agent is 0.2 cm 3 / g-2.0cm 3 / g; and / or, the specific surface area of ​​the non-carbon liquid retaining agent is 50m2 / g-1000m 2 / g.

[0007] In the embodiment of the present application, the pore volume of the non-carbon liquid retaining agent is 0.4 cm 3 / g-1.2cm 3 / g; and / or, the specific surface area of ​​the non-carbon liquid retaining agent is 50m 2 / g-300m 2 / g.

[0008] In the embodiment of the present application, the particle size D50 of the non-carbon liquid retaining agent is 0.1 μm-5.0 μm.

[0009] In an embodiment of the present application, the non-carbon liquid retaining agent includes one or more of porous alumina, porous silica, porous titanium oxide, and porous aluminum phosphate.

[0010] In an embodiment of the present application, the negative electrode active material includes a carbon-based negative electrode active material, and the carbon-based negative electrode active material includes one or more of natural graphite, artificial graphite, hard carbon, soft carbon and graphene.

[0011] In the embodiment of the present application, the porosity of the negative electrode is 10%-40%.

[0012] A second aspect of the present application provides a battery, comprising a positive electrode, a negative electrode and an electrolyte, wherein the negative electrode comprises the negative electrode provided in the first aspect of the present application.

[0013] A third aspect of the present application provides an electrical device, which includes a battery as provided in the second aspect of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 A schematic diagram of the cross-sectional structure of a negative electrode provided in one embodiment of the present application;

[0015] Figure 2 The EIS (Electrochemical Impedance Spectroscopy) spectra of Example 1 and Comparative Example 1 of the present application measured at room temperature (25° C.);

[0016] Figure 3 The EIS spectra of Example 1 and Comparative Example 1 of the present application at low temperature (-10°C);

[0017] Figure 4 This is a rate performance diagram of Example 1 and Comparative Example 1 of the present application at room temperature (25° C.);

[0018] Figure 5This is a rate performance diagram of Example 1 and Comparative Example 1 of the present application at low temperature (-10°C).

[0019] Description of Figure Numbers

[0020] 100 - negative electrode; 101 - current collector; 102 - negative electrode active layer. DETAILED DESCRIPTION

[0021] The present application is further described in detail below in conjunction with preferred embodiments, but the protection scope of the present application is not limited to the following specific embodiments.

[0022] In the present application, all professional terms have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present application.

[0023] During the charge and discharge process of lithium-ion batteries, the rapid transmission and diffusion of lithium ions are crucial to the power performance of the battery. Especially in low-temperature environments, the fluidity of the electrolyte decreases, the wettability of the battery pole piece to the electrolyte decreases, the lithium ion diffusion impedance increases, and the low-temperature performance of the battery significantly decays. In addition, in order to increase the energy density of lithium-ion batteries, it is usually adopted to increase the thickness of the active material layer and increase the compaction density of the pole piece, which will cause the porosity of the battery pole piece to decrease, thereby affecting its wettability to the electrolyte.

[0024] In order to improve the wettability of the electrolyte to the battery pole piece, some methods are to add a carbon material conductive agent with a porous structure. The porous structure of the conductive agent can effectively improve the problem of slow electrolyte conduction inside the battery pole piece, but the carbon material itself is prone to electrochemical side reactions with the electrolyte, resulting in a decrease in the battery's cycle efficiency, and the richer the porous structure of the carbon material conductive agent, the more side reactions it has, and the worse the battery's cycle efficiency. Another way is to add a functional coating with liquid-rich properties between the current collector and the active material layer, but this will cause uneven distribution of the electrolyte in the pole piece, resulting in concentration polarization and other phenomena, thereby affecting the electrochemical performance of the battery. In response to the above problems, the present application provides a negative electrode, which increases the porosity of the negative electrode by adding a non-carbon liquid retaining agent with a porous structure to the negative electrode active layer to replace part or all of the carbon material conductive agent, thereby improving its ability to retain electrolyte, reducing the diffusion impedance of the electrolyte, alleviating the polarization problem of the battery, improving the low temperature performance of the battery, and improving the rate performance and cycle life of the battery.

[0025] like Figure 1 As shown, the present application provides a negative electrode 100. The negative electrode 100 includes a current collector 101 and a negative electrode active layer 102 disposed on at least one side of the current collector 101.

[0026] In an embodiment of the present application, the negative electrode active layer 102 also includes a non-carbon liquid retaining agent, and the non-carbon liquid retaining agent has a pore structure. In some embodiments of the present application, the negative electrode active layer 102 includes a non-carbon liquid retaining agent and a conductive agent, and the mass ratio of the conductive agent to the non-carbon liquid retaining agent is less than or equal to 50%. In some specific embodiments of the present application, the mass ratio of the conductive agent to the non-carbon liquid retaining agent can be, for example, 0%. In some specific embodiments of the present application, the mass ratio of the conductive agent to the non-carbon liquid retaining agent can be, for example, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 20%, 30%, 40%, 50%. In other embodiments of the present application, the negative electrode active layer 102 includes a non-carbon liquid retaining agent and does not include a conductive agent. The present application adds a non-carbon liquid retaining agent with a porous structure to the negative electrode active layer 102 to replace part or all of the conductive agent in the negative electrode active layer. On the one hand, the non-carbon liquid retaining agent with a porous structure can effectively optimize the pore structure of the negative electrode, improve the porosity of the negative electrode, enhance the wettability of the electrolyte in the negative electrode active layer, reduce the diffusion impedance of the electrolyte, and alleviate the battery polarization problem. Especially in a low temperature environment, the fluidity of the electrolyte is significantly reduced, and the mass transfer resistance is increased. The non-carbon liquid retaining agent of the present application can increase the liquid absorption and liquid retention capacity of the negative electrode for the electrolyte, store more electrolyte medium around the negative electrode active material in advance, promote the diffusion of lithium ions in a low temperature environment, and thus improve the low temperature performance of the battery. On the other hand, compared with carbon-based liquid retaining agents and conductive agents with a porous structure, non-carbon liquid retaining agents have better chemical stability and are not easy to react with electrolytes, effectively avoiding the decline in the cycle performance and safety performance of the battery caused by side reactions and the consumption of electrolytes due to side reactions.

[0027] In the embodiment of the present application, the mass percentage of the non-carbon liquid retaining agent in the negative electrode active layer 102 is 0.5%-5%. In some embodiments of the present application, the mass percentage of the non-carbon liquid retaining agent in the negative electrode active layer 102 can be, for example, 0.5%, 1%, 2%, 3%, 4%, 5%. In the embodiment of the present application, the negative electrode active layer 102 also includes a negative electrode active material, and the mass percentage of the negative electrode active material in the negative electrode active layer 102 is 95%-9.5%. In some embodiments of the present application, the mass percentage of the negative electrode active material in the negative electrode active layer 102 can be, for example, 95%, 96%, 97%, 98%, 98%, 99%, 99.5%. By controlling the content of the non-carbon liquid retaining agent and the negative electrode active material in the negative electrode active layer within a suitable range, the electrolyte can have a good rich liquid performance while ensuring that the negative electrode has a high energy density and conductivity, thereby improving the rate performance and cycle life of the battery, especially in a low temperature environment. In the embodiment of the present application, according to the specific practical application, the negative electrode active layer 102 can be arranged on one side surface of the current collector 101, or on both sides of the current collector 101. When the negative electrode active layer 102 is arranged on both sides of the current collector 101, the mass percentage of the non-carbon liquid retaining agent in the negative electrode active layer 102 can be the same or different.

[0028] In the embodiment of the present application, the pore volume of the non-carbon liquid retaining agent is 0.2 cm 3 / g-2.0cm 3 / g; the specific surface area of ​​the non-carbon solution retaining agent is 50m 2 / g-1000m 2 In some specific embodiments of the present application, the pore volume of the non-carbon liquid retaining agent can be, for example, 0.2 cm 3 / g, 0.3cm 3 / g, 0.4cm 3 / g, 0.5cm 3 / g, 0.6cm 3 / g, 0.7cm 3 / g, 0.8cm 3 / g, 0.9cm 3 / g, 1cm 3 / g, 1.1cm 3 / g, 1.2cm 3 / g, 1.3cm 3 / g, 1.4cm 3 / g, 1.5cm 3 / g, 1.6cm 3 / g, 1.7cm 3 / g, 1.8cm 3 / g, 1.9cm 3 / g, 2.0cm3 / g; In some embodiments of the present application, the pore volume of the non-carbon liquid retaining agent is 0.4cm 3 / g-1.2cm 3 / g; the specific surface area of ​​the non-carbon liquid retaining agent can be, for example, 50m 2 / g、100m 2 / g, 150m 2 / g, 200m 2 / g、300m 2 / g, 400m 2 / g、500m 2 / g、600m 2 / g、700m 2 / g、800m 2 / g、900m 2 / g、1000m 2 / g; In some embodiments of the present application, the specific surface area of ​​the non-carbon liquid retaining agent is 50m 2 / g-300m 2 / g. Controlling the pore volume and specific surface area of ​​the non-carbon liquid retaining agent within the above range can further improve the liquid absorption and retention capacity of the negative electrode for the electrolyte, promote the diffusion of lithium ions and thus alleviate the battery polarization phenomenon, thereby improving the battery's rate performance and cycle life.

[0029] In the implementation manner of the present application, the particle size D50 of the non-carbon liquid retaining agent is 0.1μm-5.0μm, and the particle size D50 described in the present application refers to the particle size corresponding to the particle size distribution percentage of the non-carbon liquid retaining agent reaching 50%. In the implementation manner of the present application, the particle size test method of the non-carbon liquid retaining agent can refer to GB / T 24533-2019. In some specific implementation manners of the present application, the particle size of the non-carbon liquid retaining agent can be, for example, 0.1μm, 0.2μm, 0.3μm, 0.4μm, 0.5μm, 0.6μm, 0.7μm, 0.8μm, 0.9μm, 1μm, 2μm, 3μm, 4μm, 5μm. By controlling the particle size of the non-carbon liquid retaining agent within a suitable range, the present application can control the uniform distribution of the non-carbon liquid retaining agent in the negative electrode and ensure the liquid absorption and liquid retention effect of the non-carbon liquid retaining agent.

[0030] In the embodiments of the present application, the non-liquid retaining agent is porous aluminum oxide, porous silicon oxide, porous titanium oxide, or porous aluminum phosphate. In some specific embodiments of the present application, the non-carbon liquid retaining agent is porous silicon oxide. Compared with conventional porous carbon-based materials, the non-carbon liquid retaining agent selected in the present application has more stable chemical properties, can effectively inhibit the side reactions with the electrolyte, improve the utilization rate of the electrolyte, and enhance the cycle life and safety performance of the battery.

[0031] In the embodiment of the present application, the negative electrode active material includes a carbon-based negative electrode active material, and the carbon-based negative electrode active material includes one or more of natural graphite, artificial graphite, hard carbon, soft carbon and graphene. The present application selects a suitable carbon-based negative electrode active material as the negative electrode active material in the negative electrode active layer. The carbon-based negative electrode active material itself has excellent conductivity, which can provide excellent conductivity for the negative electrode active layer in the thickness direction, thereby compensating for the addition of non-carbon liquid retaining agent, which makes the conductive agent content decrease and thus causes the lack of conductivity of the negative electrode. The conductive agent mainly plays the role of increasing the conductivity of the negative electrode active layer and partially absorbing and retaining liquid in the negative electrode active layer, but it also reacts with the electrolyte at the same time, produces gas or other impurities, consumes electrolyte and reduces the safety performance and electrochemical performance of the battery. Therefore, the present application selects a suitable non-carbon liquid retaining agent to replace part or all of the conductive agent, enhances the liquid absorption and retention capacity of the negative electrode and effectively avoids the occurrence of side reactions, and selects a negative electrode active material with higher conductivity to make up for the lack of conductivity caused by the reduction of the conductive agent, so that the negative electrode has both excellent rich liquid performance and conductive performance.

[0032] In the embodiment of the present application, the negative electrode active layer 102 further includes a binder, and the binder includes one or more of carboxymethyl cellulose, styrene-butadiene rubber, and polyvinylidene fluoride. The present application can effectively bind and combine the components in the negative electrode slurry by selecting a suitable binder to form a uniform and stable negative electrode slurry, and enhance the binding force between the negative electrode active layer formed by the negative electrode slurry and the current collector, which effectively plays a buffering role when the battery expands in volume during charging and discharging.

[0033] In the implementation manner of the present application, the porosity of the negative electrode is 10%-40%. The test method of the porosity of the negative electrode can refer to GB / T21650.1-2008. In some specific implementation manners of the present application, the porosity of the negative electrode can be, but is not limited to, 10%, 15%, 20%, 25%, 30%, 35%, 40%. The present application can further improve the liquid absorption and retention capacity of the negative electrode for the electrolyte by controlling the porosity of the negative electrode within a suitable range, promote lithium ion diffusion and thus alleviate the battery polarization phenomenon, thereby improving the rate performance and cycle life of the battery.

[0034] The negative electrode provided in the present application uses a negative electrode active material with higher conductivity and a suitable non-carbon liquid retaining agent with a porous structure. Under the premise of ensuring the conductivity of the electrode, the wettability of the electrolyte in the battery electrode is enhanced, thereby enhancing the liquid retention capacity of the battery electrode, reducing the diffusion impedance of the electrolyte, alleviating the polarization problem of the battery, improving the low temperature performance of the battery, and increasing the rate performance and cycle life of the battery.

[0035] The present application also provides a method for preparing the negative electrode as described above, comprising:

[0036] S101, preparing a negative electrode slurry containing a negative electrode active material and a non-carbon liquid retaining agent;

[0037] S102, coating the negative electrode slurry on the surface of the current collector, drying and pressing to obtain a negative electrode.

[0038] In step S101, the negative electrode active material includes a carbon-based negative electrode active material, and the carbon-based negative electrode active material includes one or more of natural graphite, artificial graphite, hard carbon, soft carbon and graphene. In an embodiment of the present application, the non-carbon liquid retaining agent includes one or more of porous aluminum oxide, porous silicon oxide, porous titanium oxide, and porous aluminum phosphate. In an embodiment of the present application, the mass percentage of the negative electrode active material in the negative electrode slurry is 95%-99.5%. In some specific embodiments of the present application, the mass percentage of the negative electrode active material in the negative electrode slurry can be, for example, 95%, 96%, 97%, 98%, 98%, 99%, 99.5%.

[0039] In an embodiment of the present application, the non-carbon liquid retaining agent includes one or more of porous aluminum oxide, porous silicon oxide, porous titanium oxide, and porous aluminum phosphate. In an embodiment of the present application, the mass percentage of the non-carbon liquid retaining agent in the negative electrode slurry is 0.5%-5%. In some specific embodiments of the present application, the mass percentage of the non-carbon liquid retaining agent in the negative electrode slurry can be, for example, 0.5%, 1%, 2%, 3%, 4%, 5%.

[0040] In some embodiments of the present application, the negative electrode slurry further includes a conductive agent, which may be, for example, one or more of super P-Li, super P, acetylene black, graphene, and carbon nanotubes. In an embodiment of the present application, the mass percentage of the conductive agent in the negative electrode slurry is 0.1%-2%. In some specific embodiments, the mass percentage of the conductive agent in the negative electrode slurry may be, for example, 0.1%, 0.2%, 0.5%, 0.6%, 0.8%, 1%, 1.2%, 1.5%, 1.8%, or 2%.

[0041] In some embodiments of the present application, the negative electrode slurry further includes a binder, and the binder includes but is not limited to one or more of carboxymethyl cellulose, styrene-butadiene rubber, and polyvinylidene fluoride. In the embodiments of the present application, the mass percentage of the binder in the negative electrode slurry is 0.1%-2%. In some specific embodiments, the mass percentage of the binder in the negative electrode slurry can be, for example, 0.1%, 0.2%, 0.5%, 0.6%, 0.8%, 1%, 1.2%, 1.5%, 1.8%, 2%.

[0042] In some embodiments of the present application, the negative electrode slurry further includes a thickener, and the thickener may be any thickener known in the art. In some embodiments of the present application, the thickener may be, for example, sodium hydroxycellulose.

[0043] In step S102, the current collector may be any negative electrode current collector known in the art. In some embodiments of the present application, the current collector may be, for example, copper foil. In the embodiments of the present application, the negative electrode slurry may be applied to the surface of one side of the current collector, or to the surfaces of both sides of the current collector, according to actual application requirements.

[0044] The preparation method of the negative electrode provided in the present application has a simple preparation process, reduces production costs, shortens the production line process, and only requires one coating to obtain a negative electrode with excellent conductivity and liquid retention. The negative electrode prepared by this method has good liquid absorption and liquid retention capabilities for the electrode liquid, can effectively avoid battery polarization, and is not prone to side reactions with the electrolyte, effectively improving the battery's cycle life and safety performance.

[0045] The present application also provides a battery, the battery includes a positive electrode, a negative electrode, and a separator and an electrolyte located between the positive electrode and the negative electrode, and the negative electrode is the negative electrode provided in the previous text of the present application. In the embodiment of the present application, the battery is not limited to lithium-ion batteries and sodium-ion batteries, and the lithium-ion battery is not limited to winding lithium-ion batteries and laminated lithium-ion batteries. In some embodiments of the present application, the battery is a lithium-ion battery, and the positive electrode active material in the positive electrode is not limited to one or more of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and olivine structure lithium phosphate. In the embodiment of the present application, the diaphragm is not limited to a composite film of one or more of polyethylene, polypropylene, and polyvinylidene fluoride.

[0046] The present application also provides an electrical device, which includes the lithium-ion battery provided above. The electrical device may be, for example, an electric car, a mobile phone, a tablet computer, a laptop computer, a wearable device (a watch, a bracelet), a digital camera, etc.

[0047] The present application is further described below in multiple embodiments:

[0048] Example 1

[0049] The negative electrode active material graphite, the non-carbon liquid retaining agent porous alumina, and the binder carboxymethyl cellulose are mixed evenly with deionized water in a mass ratio of 100:2:2 to obtain a negative electrode slurry; the negative electrode slurry is evenly coated on the surface of the copper foil by a coating machine, and the negative electrode is obtained after drying and pressing; wherein the particle size D50 of the non-carbon liquid retaining agent porous alumina is 0.29 μm.

[0050] Comparative Example 1

[0051] The negative electrode active material graphite, the conductive agent super P, and the binder carboxymethyl cellulose are mixed with deionized water in a mass ratio of 100:2:2 to obtain a negative electrode slurry; the negative electrode slurry is evenly coated on the surface of the copper foil by a coating machine, and the negative electrode is obtained after drying and pressing; wherein the particle size D50 of the conductive agent super P is 0.38μm.

[0052] Pore ​​volume and surface area measurements

[0053] The non-carbon liquid retaining agent of Example 1 and the conductive agent of Comparative Example 1 were subjected to gas adsorption and desorption experiments to test the specific surface area and pore volume. Before the test, the non-carbon liquid retaining agent and the conductive agent samples were first degassed at 150°C for 6 hours, and then the adsorption and desorption of nitrogen were measured under liquid nitrogen at 77.3K to obtain the specific surface area and pore volume of the non-carbon liquid retaining agent and the conductive agent samples, respectively. The test results are shown in Table 1.

[0054] Electrochemical performance test

[0055] The negative electrode prepared in Example 1 and Comparative Example 1 was assembled into a button cell with a lithium sheet, a separator, an electrolyte and a battery shell.

[0056] Electrochemical impedance spectroscopy:

[0057] The button cell was placed at room temperature (25°C) and low temperature (-10°C) test environment temperature, under a voltage disturbance of 5mV, the test frequency range was 0.01Hz-100000Hz, and the measured EIS (Electrochemical Impedance Spectroscopy) was as follows Figure 2 , Figure 3 As shown, Figure 2 The EIS spectra of Example 1 and Comparative Example 1 measured at room temperature (25°C) are shown in FIG. Figure 3 The EIS spectra of Example 1 and Comparative Example 1 measured at low temperature (-10°C) are shown in FIG.

[0058] Discharge efficiency test:

[0059] Place the button cell at room temperature (25°C) and low temperature (-10°C) test environment temperatures, and clamp the button cell on the battery tester according to the positive and negative poles. Discharge at a constant current of 0.1C to 0.5mV, leave for 30 minutes, then charge at 0.1C to 2V, and leave for 30 minutes. Repeat the above process, using constant current discharge at 0.2C, 0.5C, 0.75C, 1.0C, 1.25C, 1.5C, 1.75C, and 2.0C, respectively, and record the discharge capacity. Taking the discharge capacity retention rate at 0.1C as 100%, calculate the discharge capacity retention rate at 0.2C, 0.5C, 0.75C, 1.0C, 1.25C, 1.5C, 1.75C, and 2.0C. Figure 4 , Figure 5 As shown, Figure 4 The rate performance diagrams of Example 1 and Comparative Example 1 measured at room temperature (25° C.) are shown in FIG. Figure 5 The graph is a rate performance diagram of Example 1 and Comparative Example 1 measured at low temperature (-10°C).

[0060] Table 1 Related performance of negative electrode and battery of Examples and Comparative Examples

[0061]

[0062] From Table 1, Figure 2 and Figure 4 It can be seen from the data that in Example 1, a non-carbon solution retaining agent is added to the negative electrode. At room temperature, compared with Comparative Example 1 in which a conventional conductive agent is added, the EIS impedance effect and rate performance of the battery prepared in Example 1 in which a non-carbon solution retaining agent is added are improved, which is significantly better than the effect of adding a conductive agent in Comparative Example 1; and according to Figure 3 and Figure 5 It can be seen that the improvement effect is more significant in a low temperature (-10°C) environment.

[0063] The preferred embodiments are described in detail above, but the present invention is not limited to the above-mentioned specific implementation modes. Under the guidance of the present application, technicians in this field can also make various specific changes without departing from the scope of protection of the present application, which all fall within the scope of protection of the present invention.

Claims

1. A negative electrode, characterized in that: The negative electrode includes a current collector and a negative electrode active layer arranged on at least one side surface of the current collector; the negative electrode active layer includes a non-carbon liquid retaining agent and a conductive agent, and the mass ratio of the conductive agent to the non-carbon liquid retaining agent is less than or equal to 50%; or, the negative electrode active layer also includes a non-carbon liquid retaining agent and does not include a conductive agent; the non-carbon liquid retaining agent has a pore structure.

2. The negative electrode according to claim 1, characterized in that The negative electrode active layer also includes negative electrode active materials, the mass percentage of the non-carbon liquid retaining agent in the negative electrode active layer is 0.5%-5%; the mass percentage of the negative electrode active materials in the negative electrode active layer is 95%-99.5%.

3. The negative electrode according to any one of claims 1 to 2, characterized in that The pore volume of the non-carbon liquid retaining agent is 0.2 cm 3 / g-2.0cm 3 / g; and / or, the specific surface area of ​​the non-carbon liquid retaining agent is 50m 2 / g-1000m 2 / g.

4. The negative electrode according to claim 3, characterized in that The pore volume of the non-carbon liquid retaining agent is 0.4 cm 3 / g-1.2cm 3 / g; and / or, the specific surface area of ​​the non-carbon liquid retaining agent is 50m 2 / g-300m 2 / g.

5. The negative electrode according to any one of claims 1 to 4, characterized in that The particle size D50 of the non-carbon liquid retaining agent is 0.1 μm-5.0 μm.

6. The negative electrode according to any one of claims 1 to 5, characterized in that The non-carbon liquid retaining agent includes one or more of porous alumina, porous silicon oxide, porous titanium oxide, and porous aluminum phosphate.

7. The negative electrode according to any one of claims 2 to 6, characterized in that The negative electrode active material includes a carbon-based negative electrode active material, and the carbon-based negative electrode active material includes one or more of natural graphite, artificial graphite, hard carbon, soft carbon and graphene.

8. The negative electrode according to any one of claims 1 to 7, characterized in that The porosity of the negative electrode is 10%-40%.

9. A battery, characterized in that: The battery comprises a positive electrode, a negative electrode and an electrolyte, and the negative electrode comprises the negative electrode according to any one of claims 1 to 8.

10. An electrical device, characterized in that: The electric device comprises the battery as claimed in claim 9.